Teacher Democratic Leadership and Student Learning Motivation: Gaya Kepemimpinan Demokratis Guru Dalam Meningkatkan Motivasi Belajar Siswa - Futhri Raudhatul Kabry; Inom Nasution (Indonesian Journal of Education Methods Development, 2026)
General Background: Teacher leadership plays a strategic role in shaping effective learning interactions and fostering student motivation and participation. Specific Background: Democratic leadership in classroom settings emphasizes student involvement, two-way communication, and shared decision-making, aligning with student-centered learning approaches. Knowledge Gap: Limited empirical attention has been given to how democratic leadership practices operate in Madrasah Tsanawiyah contexts and how they relate to both intrinsic and extrinsic student motivation. Aims: This study aims to analyze the implementation of teacher democratic leadership and examine its relationship with student learning motivation and participation. Results: Using a qualitative phenomenological approach with observations, interviews, and documentation involving teachers and students, the findings reveal that democratic leadership is consistently applied through student participation in decision-making, active discussions, and varied instructional methods. These practices are associated with increased student confidence, engagement, motivation, and active participation, alongside improved academic outcomes. Both intrinsic and extrinsic motivation are fostered through supportive classroom environments, rewards, and participatory learning strategies. Novelty: This study positions democratic leadership not merely as a leadership style but as an integrated pedagogical practice embedded in classroom learning processes. Implications: The findings suggest that adopting democratic leadership can support participatory, student-centered learning environments and can be contextually applied across diverse educational settings, although generalization should consider contextual limitations. Highlights• Student engagement increases through participatory classroom decision-making• Confidence and autonomy develop via collaborative learning practices• Academic performance shows improvement in previously low-achieving learners KeywordsTeacher Democratic Leadership; Student Learning Motivation; Student Participation; Intrinsic And Extrinsic Motivation; Qualitative Phenomenological Study